PENGARUH PERSEPSI DUKUNGAN ORGANISASI DAN PERSEPSI DUKUNGAN ATASAN TERHADAP KEINGINAN BERPINDAH DENGAN JOB EMBEDDEDNESS SEBAGAI VARIABEL MEDIASI PADA KARYAWAN BANK BRI BANDA ACEH - Fanny Silvia, Ade Irma Suryani (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
This study aims to determine the effect of perceived organizational support and perceived supervisor support to the turnover intention with the job embeddedness as a mediating variable. The sample used in this study are employees of Bank BRI in Banda Aceh. Methods This study uses a questionnaire as a research instrument. Sample simple random sampling. The method of analysis Hierarchical Linear Modeling (HLM) is used as a method of analysis to determine the variables involved. The results of this study showed that perceived organizational support significant positive effect on turnover intentions. Perceived supervisor support significant negative effect on turnover intentions. Additionally result that the job embeddedness partially mediate, and perceived organizational support on turnover intentions and perceived supervisor support partially mediate, the influence of the perceived supervisor support to the desire to move.  Keywords: Perceived Organizational Support, Perceived Supervisor Support,      Turnover Intention and Job Embeddedness